(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Anita Desai, winner of the SahityaAkademi award, was born in Mussoorie on 24th June 1937. At the age of seven,she began to write prose, mainly fiction, and published some small pieces inchildren’s magazines. Unlike R.K.Narayan, Mulk Raj Anand and BhabaniBhattacharya, who confined themselves mostly to the portrayal of outward reality,Anita Desai goes to explore the inner reality. She prefers to delve “deeper anddeeper in a character or a scene, rather than going round about it” (Jain,68).She lays emphasis on interior than on exterior characterization, on motives andcircumstances and on the invisible than visible life.